Energy Management System Optimization for GridConnected Microgrids in Presence of Energy Storage - Tabrizi, Ariyan Roshany (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
The dramatic growth in energy consumption and the governments' concern about the increase in greenhouse harmful emissions caused by fossil fuel power plants which is the main reason for global warming in recent years leads to more investments in renewable energies. One of the best ways of controlling the renewable energy resources (RESs) in an economic and reliable approach is to manage them in microgrids (MGs). In this study particle swarm optimization (PSO) and genetic algorithm (GA) is used to obtain the optimal economic dispatch (ED) in a grid connected MG in presence of photovoltaic (PV) solar energy, wind turbine (WT), microturbines (MTs), diesel generators, and energy storage system (ESS). The customers can play a major role in the energy management system by applying the demand response (DR) program which is considered in combination with other objectives in this research, power flow analysis is also investigated to check the resulted voltage level.

ÖZ: Enerji tüketimindeki çarpıcı artış ve hükümetlerin son yıllarda küresel ısınmanın temel nedeni olan fosil yakıtlı santrallerin neden olduğu sera gazı emisyonlarındaki artıştan endişe duyması, yenilenebilir enerjilere daha fazla yatırım yapılmasına neden oluyor. Yenilenebilir enerji kaynaklarını (RES) ekonomik ve güvenilir bir yaklaşımla kontrol etmenin en iyi yollarından biri, onları mikro şebekelerde (MG'ler) yönetmektir. Bu çalışmada, fotovoltaik (PV) güneş enerjisi, rüzgar türbini (WT), mikro türbinler (MTs), dizel jeneratörler ve enerji depolama sistemi (ESS) varlığında şebekeye bağlı bir mikro şebekede (MG) optimal ekonomik dağıtımı (ED) elde etmek için parçacık sürü optimizasyonu (PSO) ve genetik algoritma (GA) kullanılmıştır. Müşteriler, bu araştırmada diğer amaçlarla birlikte ele alınan talep yanıt (DR) programını uygulayarak enerji yönetim sisteminde önemli bir rol oynayabilir, elde edilen voltaj seviyesini kontrol etmek için güç akışı analizi de araştırılır.
Master of Science in Electrical and Electronic Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2022. Supervisor: Assoc. Prof. Dr. Reza Sirjani.
Keywords: Electrical and Electronic Engineering Department; Electric power systems--Wind Energy; Microgrid, Distributed Generation, Economic Dispatch, Power Flow, Photovoltaic, Wind Turbine, Energy Storage, Demand Response, Energy Management System